Challenges of Instructional Supervision of Senior High Schools in the Techiman Municipality in the Brong Ahafo Region of Ghana - Yelkpieri, Daniel; Namale, Matthew Kojo (Asian Journal of Social Sciences and Management Studies, 2016)
This study sought to investigate the challenges of supervision of teaching and learning in public Senior High Schools in the Techiman Municipality of Brong-Ahafo Region. The descriptive survey was employed to collect data. Questionnaires and interviews were the main instruments used in data collection. The data was analyzed using descriptive statistics. One hundred and twenty respondents made up of 3 headmasters of SHSs, 116 teachers and 1 external supervisor was sampled. Random and purposive sampling techniques were used in selecting participants. The study found that continuing distance learning programmes offered by the University of Cape Coast and University of Education, Winneba were the latest developments in formal training for instructional supervisors. Inadequate and irregular supplies of fuel for cars, as well as lack of payment of car maintenance allowances were among the challenges hindering effective instructional supervision in the Municipality. The study recommends among others things that the Ghana Education Service (GES) should provide headmasters with periodic in-service training programmes to keep them abreast with current trends and practices in instructional supervision.